Overall Job Satisfaction Among Managerial Employees in the Public Services Department, Malaysia - Mohd Kamil, Mohamed Hashim (1993)
The major concern of this study was to determine whether overall job satisfaction can be better determined when placed within the context of the individual's total life situation. The main objective of the study was to examine factors that contribute toward job satisfaction among managerial employees. Specifically, it undertook to determine whether selected individual attributes, selected job-related variables, and selected non-job related variables are potential determinants of overall job satisfaction. The sample Size of 160 respondents was derived from 215 accessible managerial-employees of the Public Services Department (PSD), Malaysia.